Analisis Penerapan Akuntansi Pertanggungjawaban Sebagai Alat Pengendalian Anggaran Biaya Pada Kantor Dinas Perhubungan Aceh - Cut Israeta; Syamsidar; Fitri Yunina (BE-HISZ : Journal of Economics and Accounting, 2025)
This research was conducted at the Aceh Transportation Agency in the context of the preparation of an accountability report based on Permendagri Number 55 of 2008 concerning Procedures for Administration and Preparation of Treasurer Accountability Reports. This study aims to find out and analyze the application of Accountability Accounting as a Tool for Controlling Budget Costs at the Aceh Transportation Office. The research techniques used are field research and literature research. This research method uses a descriptive method, which is a method of data that is collected, processed and classified, analyzed, and interpreted so as to obtain a clear picture of the problem being studied.The results of this study show that the implementation of accountability accounting has been effectively implemented at the Aceh Transportation Office, but there are few obstacles in the realization that occurred in the sea transportation sector with the emergence of receivables in 2017, This is due to the KMP ship operating lease. BRR in 2016 was slightly constrained by the extension of the ship operating contract. The application of accountability accounting plays a very effective role in supporting the efficiency of budget cost control and the assessment and performance of employees at the Aceh Transportation Office. Keywords: accountability accounting, cost control tools, budget.